The role of digitalization and ESG on financial performance: An empirical analysis on the Energy and Utilities sectors - Donato Morea; Gianpaolo Iazzolino; Carlo Giglio; Maria Elena Bruni; Giovanni Baldissarro; Elisa Farinelli (PLoS ONE, 2025)
In recent years authorities and regulators around the world are showing great interest in the concept of sustainability. Sustainable practices are a growing phenomenon around the world and there is increasing research on the correlation between Environmental, Social and Governance (ESG) and corporate financial performance (FP). In parallel with the increasing focus on ESG, digitalization has gained a pivotal role in the business environment. The paper wants to investigate the relationship between ESG factors and financial performance. Moreover, it tries to understand how digitalization influences that relationship. We use panel data regression using pooled ordinary least squares, fixed effects or least squares dummy variables. The panel covered by our study consists of a sample of listed companies belonging to the Energy and Utilities sectors observed from the year 2019 to 2021. In particular, our data set includes financial indicators closely related to the corporate profitability, sustainability indicators and an indicator use as a proxy of digitalization. The results provide interesting insights on how digitalization can moderate the relationship between ESG and profitability goals within the business environment, and especially the correlation that exists between sustainability and profit. The results suggest that ESG integration in corporate organizations positively affects FP because a strong ESG proposition enables businesses to grow both in existing and new markets. The findings further support the need to invest in digitalization since they show a substantial gain in financial efficiency, which can eventually boost corporate revenues. The research results support the minimization of the corporate social cost and, more generally, of social well-being. We contribute to the literature by studying the moderating role of investments in digital technologies in the context of sustainability, to understand whether or not digitalization can accelerate the impact of ESG on corporate profitability.